ANALISIS VARIASI TIPE KONDENSOR AIR CONDITIONING (AC) TERHADAP BESAR PENINGKATAN SUHU YANG DIHASILKAN - Silvilia Wahyu Kurnia Putri; Yushardi Yushardi; Bambang Supriadi (JURNAL PEMBELAJARAN FISIKA, 2018)
Condenser is an important component of Air Conditioning (AC) that serves as a heat exchanger. The heat generated by the condenser is relatively large, ranging from 37???????? - 62???????? . The amount of heat generated by the condenser can affect the human comfort. Therefore it is necessary to conduct research related Air Conditioning (AC) condenser which aims to know the heat generated by various tipes of condenser. This research was conducted by descriptive analysis by using variation of condenser tipe. From the variation of the tipe of condenser can be seen how the temperature generated by each tipe of condenser for 120 minutes of use time. The results showed that tipe 1 experienced 2 times temperature rise during measurement, the most drastic temperature rise occurred in the 65th minute with 62???????? . Condenser tipe 2 experienced 3 times temperature rise during measurement, the most drastic temperature rise occurred in the 95th minute with 45,4???????? . Condenser tipe 3 experienced 3 times temperature rise during measurement, the most drastic temperature rise occurred in the 25th minute with 55,1???????? . The results showed that there were differences in temperature produced by each condenser.Keywords: Air Conditioning, Condenser, Heat generated